A simple criterion for similar and opposite orderings - Chong, Kong-Ming (Malaysian Journal of Science, 1994)
In this paper, a simple criterion is given for similar and opposite orderings of real n-tuples. Dalam kertas ini, suatu kriteria mudah diberi bagi pentertiban berserupaan dan ber,tentangan rangkap-rangkap-n nyata. (similar/opposite orderings)